Prognostic values of fasting hyperglycaemia in non-diabetic patients with acute coronary syndrome: A prospective cohort study. Issue 6 (September 2020) - Gencer, Baris; Rigamonti, Fabio; Nanchen, David; Klingenberg, Roland; Räber, Lorenz; Moutzouri, Elisavet; Auer, Reto; Carballo, David; Heg, Dik; Windecker, Stephan; Lüscher, Thomas Felix; Matter, Christian M; et al.
Background: Controversy remains regarding the prevalence of hyperglycaemia in non-diabetic patients hospitalised with acute coronary syndrome and its prognostic value for long-term outcomes. Methods and results: We evaluated the prevalence of hyperglycaemia (defined as fasting glycaemia ⩾10 mmol/l) among patients with no known diabetes at the time of enrolment in the prospective Special Program University Medicine-Acute Coronary Syndromes cohort, as well as its impact on all-cause death, myocardial infarction, stroke and incidence of diabetes at one year. Among 3858 acute coronary syndrome patients enrolled between December 2009–December 2014, 709 (18.4%) had known diabetes, while 112 (3.6%) of non-diabetic patients had hyperglycaemia at admission. Compared with non-hyperglycaemic patients, hyperglycaemic individuals were more likely to present with ST-elevation myocardial infarction and acute heart failure. At discharge, hyperglycaemic patients were more frequently treated with glucose-lowering agents (8.9% vs 0.66%, p <0.001). At one-year, adjudicated all-cause death was significantly higher in non-diabetic patients presenting with hyperglycaemia compared with patients with no hyperglycaemia (5.4% vs 2.2%, p =0.041) and hyperglycaemia was a significant predictor of one-year mortality (adjusted hazard ratio 2.39, 95% confidence interval 1.03–5.56). Among patients with hyperglycaemia, 9.8% had developed diabetes at one-year, while the corresponding proportion among patients without hyperglycaemia was 1.8% ( p <0.001). In multivariate analysis, hyperglycaemia at presentation predicted the onset of treated diabetes at one-year (odds ratio 4.15, 95% confidence interval 1.59–10.86; p =0.004). Conclusion: Among non-diabetic patients hospitalised with acute coronary syndrome, a fasting hyperglycaemia of ⩾10 mmol/l predicted one-year mortality and was associated with a four-fold increased risk of developing diabetes at one year.